Bridging Awareness and Action: Determinants of Help-Seeking Behavior for Mental Health Among University Students - Fayza Lailla Ningtia Putri; Riastuti Kusuma Wardani; Narila Mutia Nasir; Raihana Nadra Alkaff; Ratri Ciptaningtyas (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Young people have no desire to seek professional mental health services when experiencing mental problems, they tend to seek informal services. Determinants of intentions to seek professional mental health services need to be known to determine appropriate prevention and treatment efforts in maintaining the mental health of students Objective : To determine the factors associated with the intention to seek mental health services among students of the Faculty of Health Sciences, State Islamic University Syarif Hidayatullah Jakarta Research Methods/ Implementation Methods : This cross-sectional study involved 315 randomly selected active students from the Faculty of Health Sciences at UIN Syarif Hidayatullah Jakarta. Data were collected in June 2023 and analyzed using the Chi-square test to examine associations between variables. Results : Most respondents stated that they had intentions to seek mental health services with a percentage seeking counselor services by 64.1%, seek psychologist services by 55.6%, and seek psychiatrist services by 68.3%. The study found significant associations between attitudes and the intention to seek mental health services, including counseling, psychologist, and psychiatrist services. Subjective norms were linked specifically to the intention to seek psychologist services. Perceived behavioral control was associated with the intention to seek all three types of services. Conclusion/Lesson Learned : Universities should strengthen mental health promotion by enhancing positive attitudes, perceived behavioral control, and supportive social norms to encourage help- seeking behavior among students. Efforts should include peer-based campaigns, accessible counseling services, and educational initiatives that normalize help-seeking behavior among students. Collaboration between faculty, student organizations, and mental health professionals is essential to foster a supportive environment that encourages students to seek appropriate psychological assistance.